Enhancing Students’ Environmental Care Character through the Application of “A Plate of Food” as a Learning Medium in Chemistry Education - Familia Novita Simanjuntak; Leony Sanga Lamsari Purba; Elferida Sormin; ST Fatimah Azzahra; Nova Irawati Simatupang; Putri Anjani; Lester E. Orpilla (Universitas Syiah Kuala, 2026)
Chemistry education is not only oriented towards mastering scientific concepts, but also plays an important role in shaping students' character, particularly their environmental stewardship. This study aims to describe the improvement of students' environmental stewardship through the application of the